Factors associated to sigmoidal hypertrophy in adults living at high altitude - Díaz-Lazo, Aníbal Valentín (2021)
Objective: To determine factors associated to sigmoidal hypertrophy (SH) in adults living at high altitude. Methods: A case-control study was carried-out in the Ultrasound laboratory at Hospital Regional Docente Clínico Quirúrgico Daniel Alcides Carrión, Huancayo from January 2017 to July 2019. 74 persons were included who lived at altitudes above 3000 m.a.s.l. SH was defined considering the septal thickening (> 13 mm for males and > 12 mm for females) and having a septal median thickening > a 50%. Data were collected in a questionnaire, chi-square and student´s t-test were performed and a logistic regression analysis was carried-out including variables with statistical significance at <0.05. Results: Mean age was 63 ± 16 years (range: 23-94); 41 (55.4%) were females. SH type 2 was twice more common than SH type 1; 37 patients were cases and 37 were controls. The multivariate analysis found that diabetes mellitus (OR=23.76; 95% CI: 1.61-350.7); age above 60 years old (OR=9.97; 95% CI: 1.93-51.48) and blood hypertension (OR=5.18; 95% CI: 95%: 1.19-22.59) were associated with HS (p<0.05). Conclusions: In people living at high altitude, diabetes mellitus, advanced age and blood hypertension are associated to SH.